(untitled) (Third Sector Social Economic Review, 2026)
Geographical indication products (GIPs) have become one of the fundamental instruments of both rural development and destination branding by transforming local knowledge and cultural identity into economic value. However, in Türkiye, deficiencies observed in the post-registration phase of GIPs particularly the lack of production standardization, weak institutional coordination, and inadequate marketing strategies prevent this potential from being translated into sustainable economic outcomes. This study aims to examine the institutional, managerial, and promotional factors that determine the post-registration economic effectiveness of geographical indication products, focusing on GI-certified olive oil, figs, and cotton in Aydın province. Adopting a qualitative research approach, the study employs an exploratory–explanatory case study design. Semi-structured, in-depth interviews were conducted with eight institutional stakeholders directly involved in geographical indication processes in Aydın, and the data were analyzed using Braun and Clarke’s six-phase thematic analysis method. The analysis identified four main themes: the transformation of cultural identity into economic value, the role of women producers within the geographical indication system, deficiencies in institutional governance and control mechanisms, and the need for digital promotion, storytelling, and sustainable branding. The findings indicate that the economic effectiveness of GIPs can be strengthened only when quality standardization and sustainability are ensured and supported by effective institutional coordination and digital promotional tools. The lack of inter-institutional coordination emerges as the primary factor weakening the economic impact of GIPs in Aydın. Accordingly, the study proposes structural and actionable policy recommendations, including the establishment of a joint consortium to address coordination gaps and the implementation of marketing activities within an integrated inter-institutional policy framework. The study further demonstrates that registration alone is insufficient and that post-registration processes particularly monitoring, joint promotion, and clear role distribution are decisive for achieving sustainable economic outcomes. Based on the Aydın case, the findings also suggest that geographical indication policies in Türkiye need to be supported by a more integrated and locally grounded governance model, offering a practical framework for both local stakeholders and policymakers to enhance the effectiveness of post-registration processes.